Passage of an Anterior Odontoid Screw through Gastrointestinal Tract. (17th January 2017) - Leitner, L.; Brückmann, C. I.; Gilg, M. M.; Bratschitsch, G.; Sadoghi, P.; Leithner, A.; Radl, R.
Abstract : Purpose . Anterior screw fixation has become a popular surgical treatment method for instable odontoid fractures. Screw loosening and migration are a rare, severe complication following anterior odontoid fixation, which can lead to esophagus perforation and requires revision operation. Methods . We report a case of screw loosening and migration after anterior odontoid fixation, which perforated the esophagus and was excreted without complications in a 78-year-old male patient. Results . A ventral dislocated anterior screw perforated through the esophagus after eight years after implantation and was excreted through the gastrointestinal (GI) tract. At a 6-month follow-up after the event the patient was asymptomatic. Conclusion . Extrusion via the GI tract is not safe enough to be considered as a treatment option for loosened screws. Some improvements could be implemented to prevent such an incident. Furthermore, this case is a fine example that recent preoperative imaging is mandatory before revision surgery for screw loosening.